Determination of the level of pollution of water resources - Chushkina, I. V.; Maksymova, N. M.; Чушкіна, І. В.; Максимова, Н. М. (European Scientific Platform & LLC International Centre Corporative Management, 2021)
The based on the data of laboratory studies, an integrated assessment of the quality of water resources the village of Mala Belozerka. Analytical researches have search character of an integrated estimation of level of pollution of district and are executed by a method which is offered by researchers Kryzhanovsky E.M. and Davydov I.V., is of a recommended nature and based on the algorithm of the officially approved methodology of the KND 211.1.1.106 "Organization and implementation of observations of surface water pollution (in the system of the Ministry of Energy)". According to the results of the calculation of the total pollution rate, it was found that the local water resources are characterized as dirty, despite the relatively high quality of groundwater, which is used as a source for drinking water supply to the rural population.
Keywords: integrated assessment; pollution coefficient and surface; groundwater quality; hydrochemical parameters